2020
DOI: 10.1093/jac/dkaa258
|View full text |Cite
|
Sign up to set email alerts
|

Optical maps of plasmids as a proxy for clonal spread of MDR bacteria: a case study of an outbreak in a rural Ethiopian hospital

Abstract: Objectives MDR bacteria have become a prevailing health threat worldwide. We here aimed to use optical DNA mapping (ODM) as a rapid method to trace nosocomial spread of bacterial clones and gene elements. We believe that this method has the potential to be a tool of pivotal importance for MDR control. Methods Twenty-four Escherichia coli samples of ST410 from three different wards were collected at an Ethiopian hospital and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…This was detectable thanks to the ODM method that gives a detailed fingerprint for each plasmid that can be compared between isolates. A further advantage of the ODM method is the ability to overcome the plasticity of plasmids when analyzing plasmid identity over time, with insertions and deletions, as demonstrated also in our previous studies [18,20,21].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This was detectable thanks to the ODM method that gives a detailed fingerprint for each plasmid that can be compared between isolates. A further advantage of the ODM method is the ability to overcome the plasticity of plasmids when analyzing plasmid identity over time, with insertions and deletions, as demonstrated also in our previous studies [18,20,21].…”
Section: Discussionmentioning
confidence: 81%
“…In combination with CRISPR/Cas9 restriction, we can obtain information about plasmid size, resistance gene location, and barcode in the same experiment [17]. For the characterization of plasmids, we have previously demonstrated that the ODM results correlate very well with NGS analysis [14,[18][19][20]. We have also showed its usefulness in tracking possible transmission routes in nosocomial outbreak investigations, in a neonatal polyclonal outbreak due to CTX-M-producing bacteria in Sweden, and in an ESBL E. coli ST410 outbreak in a clinical setting in Ethiopia [12,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the dynamic nature of plasmidomes, including repetitive sequences, presence of multiple replicons on a single plasmid, and presence of multiple plasmids of similar or different sizes in a cell, provide challenges to all of the mentioned techniques and might contribute to confusing or inconclusive results, giving room for the development of novel plasmid characterization methods. Optical DNA mapping (ODM), based on direct visualization of individual intact plasmid molecules using fluorescence microscopy, has shown great potential as a rapid and simple method to analyse and compare plasmids [15][16][17][18]. In ODM, large DNA molecules are labelled in a sequence specific fashion and upon stretching in nanofluidic channels and imaging by fluorescence microscopy [19], a pattern reflecting the underlying DNA sequence, a barcode, is obtained [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In ODM, large DNA molecules are labelled in a sequence specific fashion and upon stretching in nanofluidic channels and imaging by fluorescence microscopy [19], a pattern reflecting the underlying DNA sequence, a barcode, is obtained [20,21]. The method can distinguish different plasmids in a sample, based on their sizes and barcodes, which can be used for identification [17] and tracing [15,16,18], for example during a resistance outbreak. Furthermore, using the CRISPR/Cas9 system makes it possible to, in the same experiment, identify a specific (resistance) gene and determine its location along the plasmid sequence [22].…”
Section: Introductionmentioning
confidence: 99%
“…We have applied the method extensively to plasmids and in combination with Cas9 restriction, the gene causing the resistance can be identified [17]. The barcodes can be used to compare plasmids between different isolates and to compare with a theoretical sequence obtained from other sequencing techniques [18,19]. The ODM method has been successfully used in several studies of clinical relevance, including identifying potential conjugation during a resistance outbreak [20,21], or in patients with recurring urinary tract infections [22,23] as well as identifying clonal spread of bacteria in a hospital setting [19].…”
Section: Introductionmentioning
confidence: 99%